Cover Feature: Hybrid Surfactants with N‐Heterocyclic Carbene Heads as a Multifunctional Platform for Interfacial Catalysis (Chem. Eur. J. 72/2017). Issue 72 (20th October 2017) - Donner, Adrian; Hagedorn, Kay; Mattes, Lorenz; Drechsler, Markus; Polarz, Sebastian
Abstract : In daily life, surfactants are well known as detergents in the household. The cover image depicts the reported palladium‐containing amphiphile using common household elements. The central part is a washing machine in which the micellar catalysis takes place. As an example, the catalytic cycle of a C−C cross‐coupling reaction is implied. The machine (i.e., the catalytic reaction) is fed with our reported "soapy catalyst", which is illustrated by the bottle of detergent and the rising soap bubbles. More information can be found in the Communication by S. Polarz et al. onpage 18129 .